FDM preparation of bio-compatible UHMWPE polymer for artificial implant - Ramli, M. S.; Wahab, M. S.; Ahmad, M.; Bala, A. S. (Asian Research Publishing Network (ARPN), 2016)
Due to its properties of high wear, creep resistance, high stiffness and strength, Ultra-High Molecular Weight Polyethylene (UHMWPE) was developed to eliminate most metallic wear in artificial implant, which conventionally found in stainless steel, Cobalt Chromium (Co-Cr) and Titanium (Ti) alloys. UHMWPE has an ultra-high viscosity that renders continuous melt-state processes including one of the additive manufacturing processes, Fused Deposition Modeling (FDM) ineffective for making UHMWPE implant. Attempt to overcome this problem and adapting this material to FDM is by blending UHMWPE with other polyethylene including High Density Polyethylene (HDPE) and Polyethylene-Glycol (PEG) which provide adequate mechanical properties for biomedical application along with the improvement in extrudability. It was demonstrated that the inclusion of 60% HDPE fraction has improved the flowability of UHMWPE in MFI test and showing adequate thermal stability in TGA.